Facilitating Seamless Integration of Game-based Assessments in Medical Education - Saurabh RamBihariLal Shrivastava; Prateek Sudhakar Bobhate; Prithvi Brahmanand Petkar; Yugeshwari R Tiwade; Ankit K Badge (Wolters Kluwer Medknow Publications, 2024)
A health-care professional is expected to hone multiple skills that are not limited to possessing medical knowledge and clinical skills. Game-based assessments are an innovative type of assessment method that combines the features of gamification and simulation to revolutionize the delivery of medical education. These assessments have the potential to promote active engagement of students by ensuring sustained interest, which is not possible to accomplish with conventional assessments. Even though game-based assessments have immense scope in medical education delivery and have been linked with multiple merits, there are potential concerns with regard to their implementation in medical institutions. In conclusion, game-based assessments offer an immersive approach to assessing the performance of medical students, especially in the domain of critical thinking and decision-making. However, the process of planning and implementation of game-based assessment has its own share of challenges, and we must adopt a systematic approach to overcome the challenges and benefit students.